Discovering silence: shyness and self-concept in childhood - Balvín Benites de Zambrano, Gabriela Melissa (2025)
The objective of this study was to determine the relationship between shyness and self-concept in primary school children belonging to a private educational institution in Lima. In addition, we sought to identify how shyness is related to each of the dimensions of self-concept and the significant differences in the values of shyness and self-concept depending on the academicgrade and gender of the children. This study had a positivist paradigm, quantitative approach, descriptive level, basic type and non-experimental, correlational and transversal design. Therefore, the sample consisted of 100 primary school students. The Cheek and Buss Revised Shyness Scale and the Mc Daniel Piers Self-Concept Scale for children were used as instruments.The results showed an inverse and significant relationship between the variables (Rho = -0.231, p = 0.021). At the same time, significant differences were discovered in self-concept values depending on academic degree and an inverse and significant correlation between shyness and physical self-concept.